Ischiopagus Tetrapus Conjoined Twins - Nartono Kadri; Harapan Parlindungan Ringoringo; Darmawan Kartono (Indonesian Pediatric Society, 1996)
We report a case of ischiopagus tetrapus conjoined twins with one passageway (cloaca type) and bom at term by spontaneously vaginal dcliveiy, with a combined birth weight of 5000 grams. There was no history of twin in the family. During hospitalization, the conjoined twins suffered from sepsis due to ascending infection from cloacal portion, At the age of 17 days, an exploratory laparatomy and divided colostomy was performed. The postoperative complications were bleeding and sepsis. The bleeding could be properly handled only in 4 days after the treatment, whilst sepsis could not be overcome. Even in the 16th day after the operation, a peritonitis occurred followed by intestines prolapse from the edge of operative incision (on the 19th postoperative day) resulting in the death of the conjoined twins.